Energy performance evaluation of R600a/MWCNT-nanolubricant as a drop-in replacement for R134a in household refrigerator system - T. O Babarinde; S. A Akinlabi; D. M Madyira (Energy Reports, 2020)
Vapour compression refrigerator systems working with R134a are associated with high energy demand and environmental problems and refrigerator consumers' prioritise energy consumption in choosing their choice of refrigerator systems. Therefore, this research work investigated R600a in MWCNT-nanolubricant (0.4 g/L and 0.6 g/L) as a drop in replacement for R134a refrigerant in a household refrigerator system with varied mass charge of R600a (50, 60 and 70 g). The refrigerator was instrumented at the inlet and outlet of the refrigerator compressor, condenser, expansion valve and evaporator. Two bourdon type pressure gauges were connected to the compressor inlet and outlet of the system. The results were taken and evaluated and compared with the result obtained through R134a refrigerant in the system. The result showed that R600a perform better in terms of COP, power consumption and cooling capacity compared to R134a in the system with lower evaporator temperature of -11°C and power consumption of 0.0639 kW and highest COP in the system. Therefore, R6000a/MWCNT- nanolubricant can serve as a drop in replacement for R134a in the household refrigerator.
Keywords: 330; COP; Power consumption; GWP. R134a; MWCNT; R600a